Transforming Parking Systems: Exploring the Role of Manless Systems and Digitalization in Improving Operational Performance - Maulana, Ryan Yudhistira; Manafe, Leonard Adrie; Safaat, Safaat (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates, through practical measures, how the implementation of an unattended parking system at Semen Gresik Hospital has been able to boost the operational efficiency of the parking area. The system utilises automatic sensors, a mobile application, and a digital payment mechanism to address the acute problem of vehicle congestion in the hospital grounds. Data collection employed a qualitative approach and case study methodology; six informants from diverse fields were interviewed in depth to capture varied perspectives. Field findings revealed that parking search times decreased significantly and payment processes became faster, although sporadic sensor malfunctions and initial user anxiety regarding touchscreens remained as challenges. Physical queues have also decreased, and parking space utilisation has become more efficient; however, infrastructure improvements and additional public awareness campaigns remain essential. The study highlights the potential of digital technology in the healthcare sector and underscores the importance of regular technical maintenance and ongoing user education. Researchers recommend conducting similar experiments in other locations, with a greater focus on sustainability and how users can adapt to evolving technology.